2021
DOI: 10.3390/jcm10122607
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Patient-Related Safety Events during Active Mobilization for Intubated Patients in Intensive Care Units—A Multi-Center Retrospective Observational Study

Abstract: The aim of this study is to clarify the incidence and risk factors of patient-related safety events (PSE) in situations limited to intubated patients in which active mobilization, such as sitting on the edge of the bed/standing/walking, was carried out. A multi-center retrospective observational study was conducted at nine hospitals between January 2017 and March 2018. The safety profiles and PSE of 87 patients were analyzed. PSE occurred in 10 out of 87 patients (11.5%) and 13 out of 198 sessions (6.6%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…The report noted that there was little impact on medical management or treatment caused by AEs, which could be resolved by sutures for falling, replacement following tube removal, increased oxygenation and end-expiratory positive pressure, and bed rest. SAEs were also not observed in a report investigating AEs when aggressive mobilization was performed in patients with intubated tracheas in the ICU [ 13 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The report noted that there was little impact on medical management or treatment caused by AEs, which could be resolved by sutures for falling, replacement following tube removal, increased oxygenation and end-expiratory positive pressure, and bed rest. SAEs were also not observed in a report investigating AEs when aggressive mobilization was performed in patients with intubated tracheas in the ICU [ 13 ].…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that most AEs occurring during rehabilitation in the intensive care unit (ICU) setting did not warrant additional treatment, cost, or prolonged hospitalization [ 11 , 12 , 13 , 14 ]. However, for patients in acute care hospitals, reports on AEs occurring during rehabilitative care are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In a study regarding the active mobilization of intubated patients, Katsukawa et al found that the highest incidence of adverse events occurred in standing mobilizations [ 38 ]. Adverse events were correlated with highest mobilization levels under logistic regression analysis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed a post hoc analysis to investigate the association between the highest intensity level based on the IMS score or the duration from ECMO cannulation to the first mobilization and the occurrence of bleeding complications with the same covariates that were mentioned previously to evaluate the effects of rehabilitation intensity 22 …”
Section: Methodsmentioning
confidence: 99%